2021
DOI: 10.1001/jamanetworkopen.2021.31475
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration With People With Lived Experience of Mental Illness to Reduce Stigma and Improve Primary Care Services

Abstract: IMPORTANCE Collaboration with people with lived experience of mental illness (PWLE), also referred to as service users, is a growing priority to reduce stigma and improve mental health care. OBJECTIVE To examine feasibility and acceptability of conducting an antistigma intervention in collaboration with PWLE during mental health training of primary care practitioners (PCPs). DESIGN, SETTING, AND PARTICIPANTSThis pilot cluster randomized clinical trial was conducted from February 7, 2016, to August 10, 2018, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 71 publications
1
42
0
2
Order By: Relevance
“…Although outcomes were not available at the time of this review, stigma reduction among primary care workers through social contact with service has been piloted in Ethiopia, based on the REducing Stigma among HealthcAre providErs (RESHAPE) intervention developed in Nepal. The intervention components of RESHAPE were service user recovery stories and social contact; aspirational figures; myth busting; stigma didactics; and collaboration [ 76 , 77 ]. As was stated in the vision of the WHO mental health strategy [ 4 ], people with mental illness should attain a full range of health and social services free from stigma and discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Although outcomes were not available at the time of this review, stigma reduction among primary care workers through social contact with service has been piloted in Ethiopia, based on the REducing Stigma among HealthcAre providErs (RESHAPE) intervention developed in Nepal. The intervention components of RESHAPE were service user recovery stories and social contact; aspirational figures; myth busting; stigma didactics; and collaboration [ 76 , 77 ]. As was stated in the vision of the WHO mental health strategy [ 4 ], people with mental illness should attain a full range of health and social services free from stigma and discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The visual recovery narratives presented by the persons with lived experience as well as other forms of structured social interaction of persons with lived experience are incorporated into mental health trainings for PHC staff. A pilot study showed that incorporating these social contact components into PHC trainings reduced stigma, increased MHC diagnostic accuracy of HCPs, and increased willingness to endorse and deliver psychological and psychosocial treatments (i.e., not solely rely upon medication) [ 42 , 43 ]. The RESHAPE intervention is now being piloted in Tunisia, Ethiopia, India, and China.…”
Section: Discussionmentioning
confidence: 99%
“…A full description of the RESHAPE training curriculum has been published previously [ 24 ]. Table 1 presents the contents of the 10-day training for prescribers and 5-day training for non-prescribers, as well as the elements that constitute RESHAPE [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…This minimized the risk of contamination across arms. Full details of the cluster design are in the study protocol [ 22 ] and details of cluster retention are available in the pilot primary outcome publication [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation